2014
DOI: 10.1021/ja502631w
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Quadratic Nonlinear Optical Responses of Graphene by Confining White-Graphene (h-BN) Sections in Its Framework

Abstract: In an attempt to diversify the options in designing graphene-based systems bearing large second order nonlinear optical (NLO) responses of octupolar and/or dipolar character, the subject of the quadratic NLO properties of hybrid boron nitride (BN) graphene flakes is opened up. State of the art ab initio and density functional theory methods applied on a toolbox of book-text octupolar and arbitrary dipolar planar hybrid h-BN-graphene nanosized systems reveal that by confining finite h-BN sections in the interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 59 publications
(50 reference statements)
1
81
0
Order By: Relevance
“…20 Apart from atom adsorption, other techniques can be used to break the inversion symmetry of graphene sheets, such as hole formation, 21 stacking control in graphene bilayers, 22 application of non-homogeneous strain, 23 and chemical doping. [24][25][26] Among these strategies, chemical doping seems the most promising as it already represents an effective experimental mean for tuning structural and electronic properties (such as band gap and work function) of graphene. 24,25,[27][28][29] Boron nitride (BN) chemical doping of graphene has recently been successfully achieved in different configurations and concentrations: semiconducting atomic layers of hybrid h-BN and graphene domains have been synthesized, 27 low-pressure chemical-vapor-deposition (CVD) synthesis of large-area few-layer BN doped graphene (BNG) has been presented, leading to BN concentrations as high as 10%; the BN content in BNG layers has been discussed to be related to the heating temperature of the precursor, as confirmed by X-ray photoelectron spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 99%
“…20 Apart from atom adsorption, other techniques can be used to break the inversion symmetry of graphene sheets, such as hole formation, 21 stacking control in graphene bilayers, 22 application of non-homogeneous strain, 23 and chemical doping. [24][25][26] Among these strategies, chemical doping seems the most promising as it already represents an effective experimental mean for tuning structural and electronic properties (such as band gap and work function) of graphene. 24,25,[27][28][29] Boron nitride (BN) chemical doping of graphene has recently been successfully achieved in different configurations and concentrations: semiconducting atomic layers of hybrid h-BN and graphene domains have been synthesized, 27 low-pressure chemical-vapor-deposition (CVD) synthesis of large-area few-layer BN doped graphene (BNG) has been presented, leading to BN concentrations as high as 10%; the BN content in BNG layers has been discussed to be related to the heating temperature of the precursor, as confirmed by X-ray photoelectron spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies [10,27] have demonstrated that for the evaluation of the NLO properties of BCN-related species, a longrange corrected DFT method, for example CAM-B3LYP, can provide more reasonable and accurate predictions. Su et al used the CAM-B3LYP method to calculate NLO properties of h-BN-CNTs.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Karamanis et al [10] have reported the secondorder NLO responses of a series of coronene-shape h-B 12 N 12 inserting graphene nanoribbons of C n , in which the hybrid substrates of C n are hexagonal GNRs with armchair edges. However, in our study, the hybrid substrates of C n are a rectangle with the zigzag and armchair edges.…”
Section: The Comparison Of Electronic Properties Between H-bn-gnrs Anmentioning
confidence: 99%
See 2 more Smart Citations